IMPLEMENTASI ETIKA PROFESI GURU DALAM MENGEMBANGKAN MORAL ANAK USIA DINI - Indah Aryani; Sheila Zulfiani; Lutfiyanah Lutfiyanah; Muhlisin Muhlisin; Abul Mafaakhir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines how teacher professional ethics are implemented in shaping the moral character of early childhood students. Early childhood is widely acknowledged as the most formative period in human development, commonly referred to as the golden age, during which children readily absorb, internalize, and imitate values observed in their surrounding environment. Within this context, teachers hold a uniquely influential position, as they function not merely as academic instructors but as living moral models whose daily conduct whether in speech, attitude, or behavior is continuously observed and replicated by young learners. This study adopts a qualitative approach grounded in systematic literature review, drawing data from peer-reviewed scientific journals, academic books, and relevant scholarly documents focusing on teacher professional ethics and early childhood moral development. Data analysis was carried out through content analysis, involving three iterative stages: data reduction, data presentation, and conclusion drawing. The findings reveal that teacher professional ethics is concretely realized through role modeling, a sense of deep responsibility, polite and empathetic communication, and fair treatment of all students regardless of background. When these values are applied consistently and earnestly, children gradually develop a range of positive moral attributes, including honesty, self-discipline, empathy, tolerance, social care, and the capacity to respect others both within school settings and at home. Moreover, this study identifies that the successful implementation of teacher professional ethics is not determined by the teacher alone, but depends significantly on the synergy between teacher professional competence, a school environment that actively supports moral education, and the genuine involvement of parents in the child's educational journey. Obstacles such as limited teacher understanding of professional ethics, inconsistent household values, and adverse social environments are also discussed as factors that may hinder optimal moral development in early childhood.